Effect of virtual reality distraction on pain and anxiety during infiltration anesthesia in pediatric patients: a randomized clinical trial - Osama M. Felemban; Rawan M. Alshamrani; Doha H. Aljeddawi; Sara M. Bagher (BMC, 2021)
Abstract Background Different distraction techniques have been used in dentistry and have shown great results in managing anxious pediatric patients specially during local anesthesia administration. One of the recently invented techniques is virtual reality. The purpose of the study was to evaluate the effect of virtual reality distraction on anxiety and pain during buccal infiltration anesthesia in pediatric patients. Methods Healthy, cooperative 6- to 12-year-old children requiring buccal infiltration anesthesia were randomly assigned to a test or control group. In the test group, local anesthesia was administered while the subjects were watching a cartoon video using virtual reality goggles. Subjects in the control group watched a cartoon video on a screen during the administration of local anesthesia. To assess anxiety in both groups, heart rate was recorded using a pulse oximeter at five time points: (1) once the subject sets on the dental chair as a baseline; (2) when video is on; (3) at topical anesthesia application; (4) during needle insertion; (5) after the administration of local anesthesia. The face, legs, activity, cry, consolability (FLACC) behavioral pain assessment scale and the Wong-Baker FACES pain rating scale were used to assess pain. Results A total of 50 subjects were included with a mean age of 8.4 ± 1.46 years. Twenty-nine (58.0%) of the subjects were females. The mean heart rate at all time points except baseline was significantly higher among the test group compared to the control group. Multiple regression analysis showed that younger subjects and females had higher mean FLACC behavioral pain assessment scale scores (P = 0.034 and P = 0.004, respectively) regardless of the distraction technique used. Younger subjects and subjects with higher baseline heart rate reported higher mean Wong-Baker FACES pain rating scale score (P = 0.031 and P = 0.010, respectively), controlling for all other variables. Conclusion Female subjects and the younger age group were more likely to report higher pain scores during local anesthesia administration regardless of the type of distraction used. Trial registration The study was retrospectively registered in ClinicalTrials.gov with the identifier: NCT04483336 on 23/07/2020.